THE IDEA THAT DEGRADED THE WEST (Scientific journal of the Fergana State University, 2023)
In this article author argues about reasons and regularity of origination of idea of individualism. Spreading of this idea throughout Europe was the cause of enhancement of solitude, apathy of personality and appearance of new forms of family.